Does intravenous paracetamol administration affect body temperature in neonates?. Issue 3 (12th January 2011) - Hopchet, Lynn; Kulo, Aida; Rayyan, Maissa; Verbesselt, Rene; Vanhole, Christine; de Hoon, Jan N; Allegaert, Karel
Abstract : Introduction: Intravenous paracetamol (actaminophen) has recently been registered for treatment of pain in neonates but the pharmacodynamics, including effects on body temperature, have not been reported. Methods: A pooled analysis on body temperature recordings in neonates exposed to intravenous paracetamol was performed. Body temperature was recorded by skin probe and registered before and every 2 h following initiation of single or repeated intravenous paracetamol administration (up to 48 h). Repeated measures ANOVA and paired analysis were used to quantify differences following paracetamol exposure. Results: The pooled analysis was based on 99 neonates (median weight 2.7 (range 0.5–5.4) kg, median postmenstrual age 37 (range 27–50) weeks). Based on observations in 93 normothermic (<37.8°C) neonates and six neonates with fever, it was documented that paracetamol administration does not affect body temperature in normothermic patients. In neonates with fever, the median decrease (−0.8°C) is most prominent in the first 2 h (p<0.01) following paracetamol administration with subsequent further normalisation. Conclusions: Administration of intravenous paracetamol does not result in hypothermia in normothermic neonates. In those with fever, maximal temperature reduction is achieved within 2 h following paracetamol administration.